The ’Zero consumption’ phenomenon of elderly people’s sports and leisure in the Yangtze River delta region - Yamamoto, Shoko; Ito, Ayaka (Cambridge Sport Science, 2024)
This study investigates the current status of the "zero consumption" phenomenon in sports and leisure activities among elderly individuals in the Yangtze River Delta region, analyzing its characteristics and underlying causes. Data related to the consumption of sports and leisure activities among the elderly in this region were obtained through methods such as questionnaires and interviews. The results indicate that "zero consumption" in elderly sports and leisure activities is a common social phenomenon in the Yangtze River Delta region of China. It is not only a result of economic income constraints but also a consumption trend formed under the influence of various factors such as aging and declining physical fitness. While "zero consumption" does not significantly affect the elderly' s participation in sports and leisure activities, it may to some extent impact the diversification of these activities. Given the current participation status of elderly individuals in sports and leisure activities in China, it is still unable to play a crucial leading role in the development of the leisure industry as seen in developed countries.